2008
DOI: 10.3844/ajbbsp.2008.393.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Source and Carbon to Nitrogen Ratio on Hydrogen Production using C. acetobutylicum

Abstract: Problem statement: One of the main factors influenced the bacterial productivity and total yield of hydrogen is the nitrogen source and its concentration. Approach: Using different nitrogen source with different concentration on bacterial productivity of hydrogen showed to affect on both bacterial productivity of hydrogen and biomass concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 25 publications
(23 reference statements)
3
22
0
4
Order By: Relevance
“…These result showed that digester A-C had C/N ratio about 31.2, produced total quantity of biogas higher that of digester D and E which similar to the previously report by Mohd et al (2008).…”
Section: Characteristics Of Raw Materialssupporting
confidence: 90%
“…These result showed that digester A-C had C/N ratio about 31.2, produced total quantity of biogas higher that of digester D and E which similar to the previously report by Mohd et al (2008).…”
Section: Characteristics Of Raw Materialssupporting
confidence: 90%
“…Nitrogen source was generally required for enzymes, proteins, and nucleic acid synthesis—all crucial components for generation of new cells (Rughoonundun, Mohee, & Holtzapple, ). Nitrogen source could be either organic (such as yeast extract, tryptone, and peptone) or inorganic (e.g., ammonium sulfate [AMS], ammonium nitrate, and ammonium chloride) forms (Kalil, Alshiyab, & Yusoff, ). Our previous study indicated that 1 kg of C‐grade fresh longan fruit contained 25.8 ± 0.3 g sucrose, 13.9 ± 0.5 g glucose, 11.9 ± 0.3 g fructose, 51.6 ± 0.3 g total sugar, and only 0.021 ± 0.004 g of nitrogen (Nunta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the C/N ratio has a great influence on growth and metabolite production for a variety of microorganisms [27,28].…”
Section: Introductionmentioning
confidence: 99%